PENGARUH MEKANISME COPING TERHADAP STRES REMAJA - Purnama, Ni Luh Agustini; Widayanti, Marcellina Rasemi; Yuliati, Ignata; Kurniawaty, Yuni (Poltekkes Kemenkes Bandung, 2024)
Teenagers are vulnerable to experiencing stress due to various factors. The study aimed to identify the influence of coping mechanisms on stress among high school teenagers. This research was conducted at Frateran Catholic High School in Surabaya in October to January 2023. This research was a prospective study where the measurement of coping mechanisms and stress was carried out twice. The research sample was 46 teenagers in high schools in Surabaya using a simple random sampling technique. Data collection on coping mechanisms used the BriefCOPE instrument, and stress measurement used the perceived stress scale (PSS10). Data were analyzed using Spearman correlation statistical analysis and linear regression tests. There is a relationship between coping mechanisms and adolescent stress in measurement 1(p= 0.000; correlation coefficient ρ= -0.37), The correlation between coping mechanisms and stress scores in measurement 2 (p=0.02; Correlation coefficient (ρ)=-0 .34) with the degree of strength of the relationship being weak and the direction of the relationship being negative, meaning that the better the coping mechanisms, the lower the adolescent stress score. The regression test between coping mechanisms at measurement 1 and stress scores at time 2 shows R square value of 0.017, meaning 1.7% of adolescent stress is determined by coping mechanisms, other factors determine the rest. In conclusion, there was a relationship between coping mechanisms and adolescent stress in measuring the degree of strength of weak relationships and the direction of negative relationships. Recommendation for further research is to explore the role of social support on adolescent stress.